Faktor yang Mempengaruhi Tingkat Kepercayaan Penggunaan FinTech pada UMKM Dengan Menggunakan Technology Acceptance Model (TAM) - Suyanto, Suyanto; Kurniawan, Taufan Adi (Universitas PGRI Yogyakarta, 2019)
In recent years there have been alternative technology-based capital sources called FinTech, some MSMEs have begun using FinTech as an alternative source of capital, but several other MSMEs have chosen not to use FinTech because of risks such as data confidentiality, hacker attacks and fraud. This study aims to analyze the influential factors for MSMEs in utilizing technology-based FinTech as an alternative source of capital by using the technology acceptance model (TAM) by Davis by using random purposive sampling. This study shows that Ability to Use Computers (CSE), does not affect the Perception of Use (POU) on FinTech Software. The ability to use computers (CSE) has a positive effect on the Perception of Ease of Use (PEU) on FinTech Software. Perception of Ease of Use (PEU) Has a Positive Effect on the Perception of Use (POU) of FinTech Software. Perception of Use (POU) Has Positive Impact on User Attitudes (ATU) of FinTech Software. Perception of Ease of Use (PEU) does not affect the User Attitude (ATU) of FinTech Software. User Attitude (ATU) FinTech Software Has a Positive Effect on Behavior Interest (BEI). Interest in behavior (BEI) does not affect the actual use (ACU) of FinTech Software.